Tabu dan Mitos dalam Webtoon “Next Door Country” serta Pemanfaatannya dalam Pembelajaran Menulis BIPA 4 - Nurichsania, Nina Amalia; Pangesti, Fida (Jurnal Bahasa dan Sastra, 2024)
Exploring taboos and myths in the context of teaching Indonesian to foreigners will aid students in interacting more effectively when communicating with native speakers. Web comics (webtoons) can serve as an effective tool to understand them and achieve communicative competency, one of which is "Next Door Country." This qualitative descriptive study aims to explore the content of taboos and myths in the webtoon "Next Door Country" by Aditiya Wahyu Budiawan, as well as its utilization in writing instruction for BIPA 4 (intermediate level). The primary data in this study comprise visual texts from episode 28 entitled “Green Shirt," while secondary data include literature reviews obtained from government regulations and academic journals. The primary data were analyzed using Roland Barthes' semiotic analysis technique to interpret visual symbols within the webtoon, and the secondary data were qualitatively analyzed to generate insights into the application of taboos and myths in BIPA 4 learning. The findings indicate that the episode incorporates a taboo related to the Javanese myth, specifically the prohibition of wearing green clothes when going to the beach, because individuals wearing green will be taken by the guardian of the South Sea, Nyi Roro Kidul, and will not be able to return to land. This episode can be employed to achieve learning objectives of writing skills in BIPA 4 through a method of interpreting meaning based on visual illustrations in the silent comic, referring to the components forming the structure of narrative texts, namely plot, action, characterization, setting, and point of view.